Promotion Tournaments and Capital Rationing - Han, Bing; Hirshleifer, David; Persons, John C. (Review of Financial Studies, 2009)
We analyze capital allocation in a conglomerate where divisional managers with uncertain abilities compete for promotion to CEO. A manager can sometimes gain by unobservably adding variance to divisional performance. Capital rationing can limit this distortion, increase productive efficiency, and allow the owner to make more accurate promotion decisions. Firms for which CEO talent is more important for firm performance are more likely to ration capital. A rationed manager is more likely to be promoted even though all managers are identical ex ante. When the tournament payoff is relatively small, offering an incentive wage can be more efficient than rationing capital; however, when tournament incentives are paramount, rationing is more efficient.